2014
DOI: 10.1098/rspb.2013.2741
|View full text |Cite
|
Sign up to set email alerts
|

A role for iron and oxygen chemistry in preserving soft tissues, cells and molecules from deep time

Abstract: The persistence of original soft tissues in Mesozoic fossil bone is not explained by current chemical degradation models. We identified iron particles (goethite-aFeO(OH)) associated with soft tissues recovered from two Mesozoic dinosaurs, using transmission electron microscopy, electron energy loss spectroscopy, micro-X-ray diffraction and Fe micro-X-ray absorption nearedge structure. Iron chelators increased fossil tissue immunoreactivity to multiple antibodies dramatically, suggesting a role for iron in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
162
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(181 citation statements)
references
References 84 publications
13
162
4
2
Order By: Relevance
“…58). Post-mortem Fe mineralization of bone cells also occurs preferentially in/on walls59. Furthermore, pyritization of Gunflint microfossils similarly resulted of post-mortem Fe mineralization of microfossil walls and of the matrix surrounding microfossils (ref.…”
Section: Discussionmentioning
confidence: 99%
“…58). Post-mortem Fe mineralization of bone cells also occurs preferentially in/on walls59. Furthermore, pyritization of Gunflint microfossils similarly resulted of post-mortem Fe mineralization of microfossil walls and of the matrix surrounding microfossils (ref.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 PIH-treated B. canadensis and 10% formalin fixed ostrich blood vessels were embedded in LR White resin blocks after partial dehydration in 70% ethanol. Six to eight 200 nm sections were taken on a Leica EM UC6 ultramicrotome and dried overnight at 45 °C to each well of a 6-well Teflon-coated slide (Electron Microscopy Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…Despite previously proposed alternative hypotheses for the presence of primary soft-tissues in Mesozoic vertebrate fossils, such as contaminants or recent biofilms (Kaye et al, 2008), an abundance of biomolecular evidence has confirmed their initial interpretations as primary soft-tissues (Schweitzer et al, 2005(Schweitzer et al, , 2009(Schweitzer et al, , 2016Asara et al, 2007). Biochemical processes have been proposed to play a significant role in the preservation of soft osteological tissues; recently iron has been suggested as an alternative mechanism to explain the process by which primary soft-tissues can remain pliable over geologic time, by which iron from hemoglobin serves as a natural chelator to increase tissue immunoreactivity in vertebrate remains (Schweitzer et al, 2014;Lee et al, 2017). However, the presence of mineralized biofilms in vertebrate samples were osteological soft-tissues have also been recovered suggests a role in tissue preservation (Briggs, 2003;Peterson et al, 2010;Kremer et al, 2012;Raff et al, 2013Raff et al, , 2014Schweitzer et al, 2016), where biofilm crystallization in Haversian and Volkmann's canals seals natural vectors from further microbial penetration and retards subsequent metabolization of soft-tissues.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, iron has also been previously associated with soft-tissue preservation and biofilms and interpreted as pyrite framboids (Kaye et al, 2008;Peterson et al, 2010). The presence of iron associated with both preserved soft-tissues and mineralized biofilms suggests that multiple mechanisms may be involved in the preservation of primary biomolecules in fossil vertebrates (e.g., Kaye et al, 2008;Peterson et al, 2010;Schweitzer et al, 2014), including depositional chemistry, biostratinomy and sediment grain size. In order to fully explain the complex processes required to preserve primary soft-tissues in vertebrate remains over tens of millions of years, further analysis and actualistic taphonomic experimentation of biochemistry, geochemistry, and paleoenvironmental factors are needed.…”
Section: Discussionmentioning
confidence: 99%